Characteristics of CrAlSiN+DLC coating deposited by lateral rotating cathode arc PVD and PACVD process - Lukaszkowicz, Krzysztof; Sondor, Jozef; Balin, Katarzyna; Kubacki, Jerzy (Applied surface science, 2014)
Coating system composed of CrAlSiN film covered by diamond-like carbon (DLC)-based lubricant, deposited on hot work tool steel substrate was the subject of the research. The CrAlSiN and DLC layers were deposited by PVD lateral rotating ARC-cathodes (LARC) and PACVD technology on the X40CrMoV5-1 respectively. HRTEM investigation shows an amorphous character of DLC layer. It was found that the tested CrAlSiN layer has a nanostructural character with fine crystallites while their average size is less than 10nm. Based on the XRD pattern of the CrAlSiN, the occurrence of fcc phase was only observed in the coating, the texture direction 311 is perpendicular to the sample surface. Combined SEM, AES and ToF-SIMS studies confirmed assumed chemical composition and layered structure of the coating. The chemical distribution of the elements inside the layers and at the interfaces was analyzed by SEM and AES methods. It was shown that additional CrN layer is present between substrate and CrAlSiN coating. The atomic concentration of the particular elements of DLC and CrAlSiN layer was calculated from the XPS measurements. In sliding dry friction conditions the friction coefficient for the investigated elements is set in the range between 0.05 and 0.07. The investigated coating reveals high wear resistance. The coating demonstrated a dense cross-sectional morphology as well as good adhesion to the substrate.